Geographical Constraints to Economic Development in Libya (Libya Journal of Geographical Studies, 2026)
This study aimed to understand, analyze, and evaluate the geographical constraints to economic development in Libya by providing a comprehensive examination of the nature of these constraints and analyzing their roles and negative impacts on the Libyan economic reality. To address the research questions and reach its conclusions, the study employed the descriptive-analytical approach, the regional approach, and spatial analysis methods using Geographic Information Systems (GIS(. The study reached several key findings, most notably that a combination of adverse natural and human geographical conditions, coupled with severe deterioration in transportation infrastructure, logistics services, and connectivity—particularly the absence of a railway transport system—has significantly hindered economic development in Libya. This situation has been exacerbated by the lack of a national geo-economic strategy capable of enabling the economy to adapt to geographical constraints. These conditions have impeded economic development and its sustainability, prevented the equitable distribution of development benefits across all regions of the country, and ultimately led to weak development outcomes, declining gains, and reduced development targets. Based on the analysis and evaluation of these constraints, and drawing on selected geographical foundations supportive of economic development, the study proposed a national strategy for adapting to geographical constraints and capitalizing on spatial advantages, with the aim of achieving economic development objectives and ensuring their sustainability.
Keywords: Economic development; Geographical constraints; Logistics facilities; Green hydrogen; Spatial adaptation strategy